Developing Artificial Intelligence Legislation in Thailand: Lessons from the European Union - Netipatalachoochote, Stanati; Pailler, Ludovic (Journal of Human Rights, Culture and Legal System, 2025)
Artificial Intelligence (AI) is a transformative technology driving global digital transformation, significantly impacting daily life and business operations. As AI continues to advance and integrate into various sectors, the need for a well-defined regulatory framework becomes increasingly urgent. This study investigates the development of AI legal frameworks in the European Union (EU) and Thailand, analyzing their legislative approaches, priorities, and regulatory structures. Utilizing a qualitative research methodology, this study examines legislative documents, policy reports, and expert analyses to identify key similarities and differences. The findings indicate that both jurisdictions adopt a research-based and collaborative approach to AI regulation. However, while the EU prioritizes fundamental rights protection in its legal framework, Thailand places greater emphasis on fostering business growth and technological innovation, with comparatively fewer safeguards for fundamental rights. This divergence has resulted in distinct regulatory obligations, particularly for high-risk AI systems. The study concludes that Thailand could benefit from adopting aspects of the EU’s regulatory approach to achieve a more balanced framework—one that not only promotes AI-driven economic growth but also ensures stronger protections for fundamental rights and ethical considerations.